Cross Cultural Comparison of the Leadership Styles and Behaviour of Managers in the UK, USA and Southeast Asia - Roger Gill (Asian Academy of Management Journal, 1998)
Cross Cultural Comparison of the Leadership Styles and Behaviour of Managers in the UK, USA and Southeast Asia (PDF not available)